The influence of cement proportion and curing age on the mixed mode I-II fracture characteristics of cement soil - Liu, Tao; Du, Tiantian; Lu, Huaming; Hu, Baichun; Yang, Xun; Liu, Gang (Frontiers in Materials, 2024)
To study the fracture failure mechanism of cement soil under tensile-shear stress, mixed mode I-II fracture tests were conducted on cement soil semi-circular bending specimens with different cement proportions (P = 5%, 10%, 15%, 20%, and 25%) and curing ages (T = 1, 3, 5, and 7 d). The test results showed that the cracks were jagged as they propagated, and mode I stress intensity factor(KI) and mode II stress intensity factor(KII)gradually increased with the increase of cement proportion and curing age. In addition, the KII/KIC values were between 0.39 and 0.45 under different cement proportions and between 0.40 and 0.44 under different curing ages.Subsequently, the limitations of using traditional fracture criteria (MTS, S, G, and circular criteria) to describe cement soil fracture damage were identified. In contrast, the generalized maximum tangential stress (GMTS) criterion fitted the test results well, with the KII/KIC value and the crack initiation angle near the critical size rc = 1 mm curve. Based on the GMTS criterion, the rc of the cement soil crack tip micro-fracture zone was calculated as 0.3 mm to 1.9 mm.